Antioxidant effect of poleo and oregano essential oil on roasted sunflower seeds - Quiroga, Patricia Raquel (2013)
The objective was to evaluate the stability of sensory and chemical parameters in roasted sunflower seedssupplemented with oregano and poleo essential oils; and the consumer acceptability of this product. Four samples wereprepared: plain roasted sunflower seeds (Control = RS-C), and sunflower seeds added with oregano (RS-O) or poleo(RS-P) essential oils or BHT (RS-BHT). Consumer acceptance was determined on fresh samples. The overall acceptanceaverages were 6.13 for RS-C, 5.62 for RS-P, and 5.50 for RS-O (9-point hedonic scale). The addition of BHT showedgreater protection against the oxidation process in the roasted sunflower seeds. Oregano essential oil exhibited a greaterantioxidant effect during storage than poleo essential oil. Both essential oils (oregano and poleo) provided protectionto the product, inhibiting the formation of undesirable flavors (oxidized and cardboard). The antioxidant activity thatpresents essential oils of oregano and poleo could be used to preserve roasted sunflower seeds.